2011
DOI: 10.1128/aem.02843-10
|View full text |Cite
|
Sign up to set email alerts
|

GAP Promoter Library for Fine-Tuning of Gene Expression in Pichia pastoris

Abstract: A library of engineered promoters of various strengths is a useful genetic tool that enables the fine-tuning and precise control of gene expression across a continuum of broad expression levels. The methylotrophic yeast Pichia pastoris is a well-established expression host with a large academic and industrial user base. To facilitate manipulation of gene expression spanning a wide dynamic range in P. pastoris, we created a functional promoter library through mutagenesis of the constitutive GAP promoter. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
75
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(76 citation statements)
references
References 46 publications
(53 reference statements)
0
75
0
1
Order By: Relevance
“…9,19 The P GAP sequence has also been manipulated through error-prone PCR for the construction of a GAP-promoter library with strengths varying from »0,6% to 19,6-fold of that of the wild-type P GAP . 20 …”
Section: 17mentioning
confidence: 99%
“…9,19 The P GAP sequence has also been manipulated through error-prone PCR for the construction of a GAP-promoter library with strengths varying from »0,6% to 19,6-fold of that of the wild-type P GAP . 20 …”
Section: 17mentioning
confidence: 99%
“…In order to increase the yield of the recombinant protein, most investigators have focused on altering the AOX1 promoter region or alternatively using a different promoter, such as glyceraldehyde-3-phosphate dehydrogenase ( GAP ) (Hartner et al, 2008; Qin et al, 2011). Little is known about the contribution of the AOX1 5′UTR to the expression of recombinant proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Random mutated library of pAOX1 has been constructed and resulted in less glucose repression and increased activity compared to wild pAOX1 (Berg et al, 2013). The constitutive pGAP (glyceraldehyde-3-phosphate dehydrogenase promoter) served as a scaffold, and this resulted in the development of a series of promoters with a range of activity from 0.01-to 19.6-fold of wild-type pGAP activity (Qin et al, 2011). Blazeck et al (2012) reported that the combination of core promoter elements with synthetic upstream activator sequence could increase the expression level.…”
Section: Available Promoters In Non-conventional Yeast and Promoter Ementioning
confidence: 99%